Examining the Relationship Between Black Racial Identity Clusters and Postpartum Depressive Symptoms. (July 2021) - Floyd James, Kortney; Aycock, Dawn M.; Barkin, Jennifer L.; Hires, Kimberly A.
BACKGROUND: This study examined the relationship between racial identity clusters and postpartum depressive symptoms (PPDS) in Black postpartum mothers living in Georgia.AIMS: A cross-sectional study design using Cross's nigrescence theory as a framework was used to explore the relationship between Black racial identity and PPDS.METHOD: Black mothers were administered online questionnaires via Qualtrics. A total sample of 116 self-identified Black mothers were enrolled in the study. Participants ranged in age from 18 to 41 years ( M = 29.5 ± 5.3) and their infants were 1 to 12 months old ( M = 5.6 ± 3.5). The majority of mothers were married or cohabitating with their partner (71%), had a college degree (53%), and worked full-time (57%).RESULTS: Hierarchical cluster analysis identified six racial identity clusters within the sample: Assimilated and Miseducated, Self-Hating, Anti-White, Multiculturalist, Low Race Salience, and Conflicted. A Kruskal-Wallis H test determined there was no difference in PPDS scores between racial identity clusters.CONCLUSIONS: This study is the first to explore the relationship between Black racial identity clusters of postpartum mothers and their mental health. Findings emphasize the complexity of Black racial identity and suggest that the current assessment tools may not adequately detect PPDS in Black mothers. The implications for these findings in nursing practice and future research are discussed.